The Digitalization of the Russian Financial Market: The Use of Technologies of the Distributed Ledger by the Institutions of Custodian Infrastructure - Adamova, K.R.; Pokamestov, I.E. (Journal of Reviews on Global Economics, 2018)
Over the past 30 years financial markets have moved from a highly centralized to a globalized system that includes all the world's stock exchanges and other financial institutions. The global stock architecture has united the world market. Traditionally, trading in financial instruments took place between stock brokers and traders who made personal transactions on trading platforms. At that time, stock brokers were monopolists of the market, only their information, their recommendations were the only source of information for investors. This was before the dotcom revolution, when communication became simple and accessible to everyone. Trade has been transformed from physical to electronic form, today you can buy securities, currencies and any derivatives in any quantity, at any time and from anywhere in the world. Development of blockchain technologies is integrated into financial transactions. Financial intermediaries are forced to follow the market and actively introduce new technologies in their processes. This article will consider the possibility of using the technology of the distributed ledger by institutions of custodian infrastructure. Today, a number of Russian financial institutions are developing their own projects using blockchain.